Efficiency of dendritic mycorrhizal fungi (AM) in stimulating non-enzymatic antioxidants in tomato roots infected with Fusarium oxysporum f.sp.lycopersici (Journal of the College of Basic Education, 2022)
The present study was Conducted to evaluate the effect of amixture of three species of arbuscular mycorrhizal fungi ( Glomus etunicatum , G. leptotichum and Rhizophagus intraradices ) in inducing the non-enzymatic antioxidants of tomato roots infected with Fusarium oxysporum f.sp. Lycopersici wich cause Fusarial wilt disease , and planted for 10 weeks in the presence of the organic matter ( peatmose) , using pot cultures in aplastic green house , Results indicated significant reduction of disease incidence percentage and infection rate of roots infected with the pathogen 4 weaks after mycorrhizal colonization in all treatments ( single , dual and trial interactions) . on the other hand mycorrhizal colonization of the roots in the presence of organic matter and pathogen after 4 weaks of pathogen infection resulted in significant increase of proline content, total phenol , malondialdehyde , glutathione and hydrogen peroxide of roots in all treatment ( single , dual and trial interaction ) . The trial treatment ( M ×F.o.l .×O) Showed the highest content of all antioxidants tested followed by the dual ( M ×F.o.l .) , whereas the lowest content of all antioxidants for all treatments was shown at the time of plantation ( OW+ ) in the presence of the pathogen